Pairs of paths and critical points - Florin Caragiu; Ioana Caragiu (International Journal of Mathematics and Mathematical Sciences)
Two sufficient conditions are presented, in terms of the values taken by a holomorphic function f(z) on a pair of smooth paths intersecting at a point z0 in its domain, implying that f′(z0)=0.